The Role of Automation Technology and New Skills Affecting Employee Work Performance in Industrial Factories: A Case Study of Nittan (Thailand) Co., Ltd.: The Role of Automation Technology and New Skills Affecting Employee Work Performance in Industrial Factories: A Case Study of Nittan (Thailand) Co., Ltd. - Ketsa, Suphol; Kulsawat, Teera (RATANABUTH JOURNAL, 2026)
This research aimed to: 1) examine the level of employee work performance at Nittan (Thailand) Co., Ltd.; and 2) investigate the effects of automation technology and new skills on employee work performance in an industrial setting. This study employed a quantitative research design. The sample consisted of 189 employees of Nittan (Thailand) Co., Ltd., determined using the Krejcie and Morgan approach at a 5% margin of error. Stratified random sampling was applied according to department, followed by simple random sampling within each department. The research instrument was a five-point rating scale questionnaire with a reliability coefficient of 0.81. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as Structural Equation Modeling (SEM) using the LISREL program. The findings revealed that the overall level of employee work performance was high. The causal model demonstrated a good fit with the empirical data (relative chi-square = 1.05, CFI = .99, GFI = .95, AGFI = .92, RMSEA = .02, SRMR = .02, and RFI = .98), meeting all major goodness-of-fit criteria. Automation technology (TE = .50) and new skills (TE = .49) were found to have statistically significant effects on employee work performance. The coefficient of determination for employee work performance was .96 (R² = .96), indicating that automation technology and new skills jointly explained 96% of the variance in employee work performance. These findings suggest that integrating automation technology into production processes, together with developing employees’ new skills, can effectively enhance work performance in terms of work quantity, work quality, responsibility, efficient resource utilization, and workplace collaboration.